2009
DOI: 10.1097/jto.0b013e31819c9a59
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial Lipomas: Rare Benign Lung Tumors, Two Case Reports

Abstract: Endobronchial lipoma is a rare benign lung tumor. Here we present two cases. One case is the first report of the association of and endobronchial lipoma with a hilar lipoma. We discuss the epidemiology, difficulties in establishing the diagnosis, and the management of this rare condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 5 publications
1
27
0
Order By: Relevance
“…Endobronchial lipomas account for 0.1%-0.5% of lung tumours (1) and about 13% of benign lung tumours. (2) Patients present in middle age and are usually male, with a strong male predominance (male-to-female ratio of 45:7).…”
Section: Dear Sirmentioning
confidence: 99%
“…Endobronchial lipomas account for 0.1%-0.5% of lung tumours (1) and about 13% of benign lung tumours. (2) Patients present in middle age and are usually male, with a strong male predominance (male-to-female ratio of 45:7).…”
Section: Dear Sirmentioning
confidence: 99%
“…Only 5% of them are benign, of which ninety percent are adenomas (mucous cell adenoma, pleomorphic adenoma and oncocytoma) or hamartoma [3]. Lipomas constitute 3.2-9.5% of all benign endobronchial tumors [3]. They have an incidence of 0.1-0.5% indicating that they are extremely rare [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…Bronchoscopy also often does not provide a definite diagnosis due to the fibrous capsule of the lesion. However, CT is highly specific and sensitive in the detection of adipose tissue and CT finding of a pedunculated homogenous lesion with attenuation of around 100 HU can lead to definitive diagnosis of endobronchial lipoma [3,7]. However, endobronchial hamartomas which can contain fat besides cartilage, fibrous and epithelial tissue, also appear as a fatty mass on CT [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bronchial lipoma is extremely rare benign tumor with an incidence from 0.1% to 0.5% of all lung tumors and 1.4-13.0% of benign tumors of the lung (61). In a recent review of the English and Japanese literature on endobronchial lipomas, Fujino et al reported 95 cases.…”
Section: Lipomamentioning
confidence: 99%